The statutes of a parish - Renken, John A. 1953- (2010)
vgl. can. 922.1 CCEO
Keywords: Katholische Kirche; Katholische Kirche; Katholische Kirche; Katholische Kirche; Katholische Kirche; Katholische Kirche; Katholische Kirche; Pfarrei; Pfarrei; Juristische Person; Satzung